Partitioning and drivers of aquatic insect beta diversity in mountain streams - Bispo, Pitágoras C. [UNESP] (2021)
In recent years, interest in considering multiple facets of diversity has grown among community ecologists. Biological communities are complex systems, and exploring multiple facets can help reveal the main processes that drive diversity patterns. In this paper, we used a metacommunity framework to study the taxonomic, phylogenetic, and functional facets of beta diversity in assemblages of aquatic insects (Ephemeroptera and Trichoptera) with data from mountain streams collected in 2 study systems in the Mata Atlântica (Atlantic Forest) of Brazil: 22 streams from the northern coast of the São Paulo State and 33 streams from the southern coast of São Paulo State. We assessed the following: 1) the relative contributions of turnover and nestedness for different facets of beta diversity and 2) the relationships between environmental and spatial factors on the different facets and components of beta diversity. Beta diversities were high for all facets, and turnover was the main component of the taxonomic (based on incidence and abundance) and phylogenetic facets. In contrast, nestedness was an important component of the functional facet. The roles played by environmental and spatial variables varied erratically between the studied facets, insect orders, and study systems. Environment and space were both poor predictors of the different facets of beta diversity. Our results demonstrated that the difficulty of explaining the taxonomic beta diversity observed in other studies of aquatic insect stream metacommunities also arises for other facets of beta diversity (phylogenetic and functional). The high values of turnover found for most facets suggest that conservation strategies should seek to preserve as many streams as possible within a hydrographic network.